miR-744-5p Inhibits Multiple Myeloma Proliferation, Epithelial Mesenchymal Transformation and Glycolysis by Targeting SOX12/Wnt/β-Catenin Signaling - Guo, Bingling (Onco Targets Ther, 2021)
PURPOSE: This study investigated the function and molecular mechanisms of miR-744-5p in multiple myeloma (MM). METHODS: miR-744-5p and SRY-related high-mobility-group box 12 (SOX12) expression in clinical tissues and MM cells was monitored by quantitative real-time polymerase chain reactions and Western blot. miR-744-5p expression in MM cells was regulated by transfection. Cell proliferation was researched by cell counting kit-8 assay and plate clone formation experiment. Transwell experiment was utilized for migration and invasion detection. Glycolysis test was conducted for the detection of glucose uptake and lactate production of MM cells. The relationship between miR-744-5p and SOX12 was determined by dual-luciferase reporter gene assay and RNA pull-down experiment. In vivo experiment was conducted using nude mice. RESULTS: miR-744-5p expression was reduced in MM patients (P<0.01). Low miR-744-5p expression was associated with lower 60-month survival in MM patients (P=0.0402). miR-744-5p overexpression inhibited MM cells proliferation, invasion, migration, glucose uptake, lactate production, and epithelial mesenchymal transformation (EMT) (P<0.01). miR-744-5p directly inhibited SOX12 expression. miR-744-5p silencing promoted MM cells proliferation, invasion, migration, glucose uptake, lactate production, and EMT by elevating SOX12 (P<0.01). miR-744-5p inhibited the growth of MM xenograft tumors in vivo (P<0.001). CONCLUSION: miR-744-5p inhibits MM cells proliferation, invasion, migration, EMT, and glycolysis by targeting SOX12/Wnt/β-catenin.